Video; the reflexive medium - Spielmann, Yvonne; Welle, Anja; Jones, Stan; Malina, Roger F. (Cambridge (MA) : The MIT Press, 2008)
Introduction: The audiovisual medium. ##pt. I. Video, a technology, a medium. ##Media-theoretical considerations ; The visualization debate ; Preconditions of the technology and the apparatus ; Matrix phenomena -- ##pt. II. The reflexive medium. ##Experimental phase ; Guerilla television ; Artistic video ; Excursus on the relationship of film, video and computer ; Experimental video ; Video cultures -- ##pt. III. Video aesthetics. ##Apparatus, self-reflection and performance : Vito Acconci and Dennis Oppenheim ; Picture, reproduction, media images : Ulrike Rosenbach, Joan Jonas and Valie Export ; Video/TV : Nam June Paik and Dara Birnbaum ; Video, photo and film : Klaus vom Bruch and Peter Campus ; Structural video : Michael Langoth, Les Levine, Jean-François Guiton, Richard Serra and Dieter Kiessling ; Musicalisation in video : Robert Cahen ; Layering and condensing : Peter Callas ; Video scratching : Martin Arnold and Raphael Montañez Ortiz ; Video void : David Larcher ; Micro/macro dimensions : Nan Hoover ; Picture, text, voice and writing : Gary Hill ; Video and computers : Steina and Woody Vasulka ; Video and virtual environment : Lynn Hershman ; Video, poetics and hypermedia : Bill Seaman ; Video installations : Eija-Liisa Ahtila, Chantal Akerman, Gillian Wearing -- ##Outlook : complexity and Interactivity.
boek